Effects of carbohydrate dose and frequency on metabolism, gastrointestinal discomfort, and cross‐country skiing performance. Issue 9 (27th August 2015) - Stocks, B.; Betts, J. A.; McGawley, K.
Abstract : This study investigated carbohydrate ingestion of varied doses and frequencies during a simulated cross‐country skiing time trial. Ten men and three women (age: 30 ± 7 years; V ˙ O 2 m a x : 59.6 ± 5.7 mL/kg/min) completed four, 30‐km classic technique roller skiing time trials on a treadmill. A 1:1 maltodextrin‐fructose carbohydrate solution was provided at high (2.4 g/min; HC) and moderate (1.2 g/min; MC) ingestion rates, each at high (six feeds; HF) and low (two feeds; LF) frequencies. In the LF trials, blood glucose was elevated following carbohydrate ingestion (at 4 and 19 km) but was reduced at 14 and 29 km compared with HF strategies ( P  ≤ 0.05). Gastrointestinal discomfort was higher in HC‐LF compared with all other trials ( P  ≤ 0.05). Whole‐body lipid oxidation was lower and carbohydrate oxidation was higher in LF compared with HF trials ( P  ≤ 0.05). While performance time was not significantly different between trials (140:11 ± 15:31, 140:43 ± 17:40, 139:12 ± 15:32 and 140:33 ± 17:46 min:s in HC‐HF, HC‐LF, MC‐HF, and MC‐LF, respectively; P  > 0.05), it was improved with trial order ( P  < 0.001). There was no effect of order on any other variable ( P  > 0.05). Altering carbohydrate dose or frequency does not affect cross‐country ski performance. However, low‐frequency carbohydrate ingestion resulted in poorer maintenance of euglycemia, reduced lipid oxidation, and increased gastrointestinal discomfort.